2018
DOI: 10.7554/elife.36131
|View full text |Cite
|
Sign up to set email alerts
|

Adult zebrafish Langerhans cells arise from hematopoietic stem/progenitor cells

Abstract: The origin of Langerhans cells (LCs), which are skin epidermis-resident macrophages, remains unclear. Current lineage tracing of LCs largely relies on the promoter-Cre-LoxP system, which often gives rise to contradictory conclusions with different promoters. Thus, reinvestigation with an improved tracing method is necessary. Here, using a laser-mediated temporal-spatial resolved cell labeling method, we demonstrated that most adult LCs originated from the ventral wall of the dorsal aorta (VDA), an equivalent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 79 publications
3
31
0
Order By: Relevance
“…This phenotype is reminiscent of that of Il34 mutant mice that selectively lack microglia and Langerhans cells (Greter et al, 2012; Wang et al, 2012). Previous studies claimed skin mpeg1 + hematopoietic branched cells in zebrafish to be Langerhans cells (He et al, 2018; Lin et al, 2019). It remains unclear whether these are true Langerhans cells, as there is no known zebrafish ortholog of langerin (CD207), the main marker of LCs in humans and mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenotype is reminiscent of that of Il34 mutant mice that selectively lack microglia and Langerhans cells (Greter et al, 2012; Wang et al, 2012). Previous studies claimed skin mpeg1 + hematopoietic branched cells in zebrafish to be Langerhans cells (He et al, 2018; Lin et al, 2019). It remains unclear whether these are true Langerhans cells, as there is no known zebrafish ortholog of langerin (CD207), the main marker of LCs in humans and mice.…”
Section: Discussionmentioning
confidence: 99%
“…We found that primitive myelopoiesis is initially csf1r -independent, although csf1r DM embryonic macrophages subsequently ceased to divide and failed to colonize embryonic tissues. Surprisingly, a detailed examination of csf1r DM larval zebrafish revealed another wave of mpeg1+ cells in the skin from 15-days of development onwards, but these cells lacked the branched morphology typical of Langerhans cells (He et al, 2018). Using fate mapping and gene expression profiling, we identified csf1r DM mpeg1+ cells as metaphocytes, a population of ectoderm-derived macrophage-like cells recently reported in zebrafish (Alemany et al, 2018a; Lin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The sex of zebrafish embryos is difficult to confirm scientifically so the information is not provided. ABSR wild-type, Tg(Xla.Tubb:bcl-2) (Xu et al, 2016), Tg(hsp70:mCherry-T2a-CreER T2 ) (Hans et al, 2011), Tg(mpeg1:DsRedx) short for Tg(mpeg1:loxP-DsRedx-loxP-GFP) hkz15Tg (He et al, 2018), Tg(mpeg1:kaede) hkz16Tg , Tg(Xla.Tubb:csf1a) hkz17Tg , Tg(Xla.Tubb:csf1b) hkz18Tg , Tg(Xla.Tubb:il34) hkz19Tg , csf1ra j4e1 (Parichy et al, 2000), csf1a hkz9 , csf1b hkz10 , and il34 hkz11 are used in this study. All animal experiments were performed under approval from the Hong Kong University of Science and Technology's Animal Studies Committee.…”
Section: Star+methodsmentioning
confidence: 99%
“…1a). Prior to this work, Kupffer cells were thought to be missing or sparse in zebrafish and other teleost species [31,32], but recent work tracing adult zebrafish Kupffer cells to their hematopoietic origin [33], and the data presented here collectively provide the first evidence for the prevalence of Kupffer cells in the zebrafish liver akin to their mammalian counterpart. Since the brain-LPS injection and subsequent analysis were conducted at 4 dpf, before the establishment of Kupffer cells, the presence of macrophages in the liver was likely because of active recruitment of peripheral macrophages and monocytes.…”
Section: Kupffer Cell Establishmentmentioning
confidence: 99%